MASALAH BELAJAR YANG DIALAMI MAHASISWA PENERIMA BEASISWA BIDIK MISI FIP UNP - salim, syukri (Konselor, 2013)
Learning problems can hamper students in the lecture process. Student learning problems include: mastery of subject matter prerequisite subjects (P), study skills (T), a learning tool (S), self (D), environmental and socio-emotional learning (L). This study aimed to describe the learning problems experienced by students recipients BIDIK MISI FIP UNP. This research is descriptive quantitative kind. The research population was students BIDIK MISI FIP UNP. The sample in this study as many as 66 people were selected by Proportional Random Sampling technique. Instrumen used is AUM PTSDL Format 1 Students. The data analysis technique used is descriptive percentage. The results revealed that: 1) Students BIDIK MISI FIP UNP problematic aspects of prerequisite mastery of subject matter, 2) very problematic aspect of learning skills 3) on aspects of learning tools, students BIDIK MISI FIP UNP enough viewfinder, 4) problematic aspects of the self, and 5) environmental aspects and socio-emotional learning is problematic. Keywords: Learning Problems.